Quantification of intrinsic regulatory factors refines human hematopoietic progenitor definitions and reveals early erythroid lineage priming - Patricia Favaro; David R. Glass; Luciene Borges; Reema Baskar; Avery Lam; Warren Reynolds; Daniel Ho; Trevor Bruce; Dmitry Tebaykin; Thomas Koehnke; Vanessa M. Scanlon; Ilya Shestopalov; et al. (Cell Reports, 2025)
Summary: Hematopoietic stem and progenitor cell (HSPC) transplantation is an essential therapy for hematological conditions, but finer definitions of human HSPC subsets with associated function could enable better tuning of grafts and more routine, lower-risk application. To deeply phenotype HSPCs, following a screen of 328 antigens, we quantified 41 surface proteins and functional regulators on millions of CD34+ and CD34− cells, spanning four primary hematopoietic tissues: bone marrow, mobilized peripheral blood, cord blood, and fetal liver. We propose more granular definitions of HSPC subsets and present detailed differentiation trajectories of erythroid and myeloid lineages. These aspects of our revised human hematopoietic model are validated with corresponding epigenetic analysis, in vitro clonal differentiation assays, and an in vivo cell tracing model. Overall, we demonstrate the utility of using molecular regulators as surrogates for cellular identity and functional potential, providing a framework for description, prospective isolation, and cross-tissue comparison of HSPCs in humans.